Study guides

☆☆

Q: 2x plus 3x equals

Write your answer...

Submit

Still have questions?

Related questions

2x + 3x + 6 = 5x + 6

3x

3x+56 = 2x+4 3x-2x = 4-56 x = -52

3x+5 = 2x+13 3x-2x = 13-5 x = 8

3x + 8 = 2x +28 3x - 2x = 28 - 8 x=20

3x - 3 = 2x + 6 3x = 2x + 9 x = 9

2x + 2 = 3x - 57 = x

-3x + (-18) = 2x + 7 +18 +18 -3x = 2x +25 -2x -2x -5x = 25 ----- ----- -5 -5 x=-5 *------- equals a division line

3x + 5x = 2x + 28x = 2x + 26x = 2x = (2/6) = 1/3

yes

3x

3x + 2x = 40 5x = 40 x = 8

3x - 12 = -2x + 235x = 35 so x = 7

2x+3 = 3x+5 2x-3x = 5-3 -x = 2 x = -2

5k

2x+5=3x+1 -x=-4 x=4

3x - 2x + 4 = 0 3x - 2x = -4 x = -4

3x+4 = 2x-3 3x-2x = -3-4 x = -7

2x - 6x + 3x = -412x - 3x = -41-1x = -41x = 41

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

3x+7=2x-5 x=-12

2x-12

-3x+2 = 2x-8 8+2 = 2x+3x 10 = 5x x = 2

-3x+7=2x-18 ---> 7+18=2x-3x ----> 25=5x ----> x=5

2x+12-3x = 5 2x-3x = 5-12 -x = -7 x = 7